2014
DOI: 10.1021/jp5066677
|View full text |Cite
|
Sign up to set email alerts
|

Structural Changes Observed during the Reversible Hydrogenation of Mg(BH4)2 with Ni-Based Additives

Abstract: The decomposition and rehydrogenation of γ-Mg (BH 4 )

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
57
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 36 publications
(77 reference statements)
4
57
0
Order By: Relevance
“…The addition of several TM-compounds has indeed resulted in improved hydrogen storage properties of stable borohydrides and related composites, including decrease in Tdec [35,41], in some cases remarkably by as much as 200 °C [36]. Enhancement of the desorption and absorption reactions kinetics [26,42], improved hydrogen purity, reversibility [37] and borohydride synthesis from the decomposition products [39] has also been documented.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…The addition of several TM-compounds has indeed resulted in improved hydrogen storage properties of stable borohydrides and related composites, including decrease in Tdec [35,41], in some cases remarkably by as much as 200 °C [36]. Enhancement of the desorption and absorption reactions kinetics [26,42], improved hydrogen purity, reversibility [37] and borohydride synthesis from the decomposition products [39] has also been documented.…”
Section: Introductionmentioning
confidence: 96%
“…In our previous works [26,42] we have shown that Ni-and Co-based additives have an effect on the kinetics of hydrogen desorption and absorption in γ-Mg(BH4)2 [13]. Ex-situ X-ray absorption spectroscopy (XAS) studies have shown that the additives were chemically modified to compounds similar to Ni-and Co-borides after first decomposition of Mg(BH4)2.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, the dehydrogenation temperature is reduced to 360 • C. However, the hydrogen capacity of the system is still low, i.e., 4.5 wt %. The effect of additives on the reversibility of Mg(BH 4 ) 2 has been an object of intensive investigation [101,[183][184][185][186][187][188]. The result of the doping seems to be a sensible acceleration of hydrogenation and dehydrogenation processes.…”
Section: Nabhmentioning
confidence: 99%